Rapid monitoring in vaccination campaigns during emergencies: the post-earthquake campaign in Haiti - Rainey, Jeanette J (World Health Organization, 2013)
PROBLEM: The earthquake that struck Haiti in January 2010 caused 1.5 million people to be displaced to temporary camps. The Haitian Ministry of Public Health and Population and global immunization partners developed a plan to deliver vaccines to those residing in these camps. A strategy was needed to determine whether the immunization targets set for the campaign were achieved. APPROACH: Following the vaccination campaign, staff from the Ministry of Public Health and Population interviewed convenience samples of households – in specific predetermined locations in each of the camps – regarding receipt of the emergency vaccinations. A camp was targeted for “mop-up vaccination” – i.e. repeat mass vaccination – if more than 25% of the children aged 9 months to 7 years in the sample were found not to have received the emergency vaccinations. LOCAL SETTING: Rapid monitoring was implemented in camps located in the Port-au-Prince metropolitan area. Camps that housed more than 5000 people were monitored first. RELEVANT CHANGES: By the end of March 2010, 72 (23%) of the 310 vaccinated camps had been monitored. Although 32 (44%) of the monitored camps were targeted for mop-up vaccination, only six of them had received such repeat mass vaccination when checked several weeks after monitoring. LESSONS LEARNT: Rapid monitoring was only marginally beneficial in achieving immunization targets in the temporary camps in Port-au-Prince. More research is needed to evaluate the utility of conventional rapid monitoring, as well as other strategies, during post-disaster vaccination campaigns that involve mobile populations, particularly when there is little capacity to conduct repeat mass vaccination.